9 - Re-envisioning the Academic Profession in the Shadow of Corporate Managerialism* - Stewart, Peter (Journal of Higher Education in Africa, 2007)
This article argues that global and South African changes to universities have re- sulted in change being led by corporate managerialism. This has created new roles and new difficulties for academics, who display signs of stress and low morale. The article examines the case of UNISA, together with international and South African evidence on academics. The changing class status of academics is also examined. The negative yet pervasive psychical consequences of intrusive bureaucracy are discussed. The concept of ‘knowledge production’ is then subjected to a critique to outline a core academic role involving, firstly, using disciplinary rigour to open up debates and facilitate openness to the density of the real world, and secondly, work- ing through transferential dependences in teaching and research. It concludes by recommending the formation of a ‘critical collegial movement’ which will explore what new academic role is appropriate to the new situation, and which will take action to empower academics through increased collegiality.